Micronized Dehydrated Human Amnion Chorion Membrane Injection in the Treatment of Knee Osteoarthritis—A Large Retrospective Case Series - Alden, Kris J.; Harris, Stan; Hubbs, Brandon; Kot, Kimberly; Istwan, Niki B.; Mason, David (The Journal of Knee Surgery, 2019)
Osteoarthritis (OA) of the knee is a leading cause of chronic pain and disability in the United States. Current treatment options primarily target OA symptoms reserving surgical intervention and knee replacement for those who fail conservative measures. With average age of patients with knee OA decreasing, regenerative treatment approaches to reduce symptoms, increase quality of life, and delay the need for surgical intervention are increasingly sought. Human amniotic membrane contains growth factors and cytokines, which promote epithelial cell migration and proliferation, stimulate metabolic processes leading to collagen synthesis, and attract fibroblasts, while also reducing pain and inflammation. Micronization of the tissue allows for suspension in normal saline and injection. We conducted a retrospective review of 100 knees treated for symptomatic OA with micronized dehydrated human amnion/chorion membrane (mdHACM) and followed for 6 months. Our purpose is to present our experience and patient outcomes. Data were abstracted from electronic medical records of 82 consecutive OA patients (100 knees) injected with 100 mg mdHACM. Patient age, gender, adverse events and routinely collected Knee Injury and Osteoarthritis Outcome Score (KOOS) were evaluated. Effectiveness of mdHACM treatment was measured by serial KOOS at baseline, and posttreatment at 6 weeks, 3, and 6 months. Overall mean KOOS for the cohort was 40 at baseline, improving to 52, 62, and 65 at 6 weeks, 3 months, and 6 months post-mdHACM injection. Percent increases were 32, 56, and 65%, respectively. Quality of life and sports/recreation domains improved by 111 and 118%, respectively, at 6 months. Pain scores improved by 67% at 6 months. All scores improved throughout the observation period. The most common adverse event was pain after injection lasting 2 to 7 days, observed in 68% of cases. This represents the largest single-physician experience with mdHACM for treatment of knee OA reported to date. Injectable mdHACM appears to be a potentially useful treatment option for knee OA patients. Controlled studies are underway to confirm these observations.
Keywords: amniotic membrane; dehydrated human amnion/chorion membrane; osteoarthritis